2011
DOI: 10.1590/s0100-40422011000100013
|View full text |Cite
|
Sign up to set email alerts
|

Esterois como indicadores do acúmulo de esgotos domésticos em sedimentos de um sistema estuarino-lagunar tropical (Mundaú-Manguaba, AL)

Abstract: , AL). The history of sewage contamination in the Mundaú-Manguaba estuarine lagoon system (NE Brazilian coastal zone) was evaluated through the concentration of sterols in sediment cores. The concentration of coprostanol increased towards the surface sediments, with the maximum of 5.65 µg g -1 at 0-2 cm sediment layer in Mundaú. Manguaba exhibited a lower level of contamination. The ratio cholestanol/cholesterol suggested degradation of coprostanol only before the burial of organic matter in the sediment. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 21 publications
1
1
0
2
Order By: Relevance
“…Comparing our values with other studies (Table 3), it was observed that coprostanol concentrations and the ratio (5β/5β + 5α) were higher than in some studies carried out in the North, Southeast and South regions of Brazil, such as the Mundaú-Manguaba Lagoon, in Alagoas, Sepetiba Bay in Rio de Janeiro, Patos Lagoon in Rio Grande do Sul and in Concepcion Bay in Chile. 48,[54][55][56] Similar comparison was also found in n-alkanes quantification at Mundaú-Manguaba and Sepetiba Bay. Patos Lagoon in Rio Grande do Sul is the largest coastal lagoon that suffers with great anthropic pressure from urban, rural and industrial activities.…”
Section: Distribution Of Sterolssupporting
confidence: 76%
“…Comparing our values with other studies (Table 3), it was observed that coprostanol concentrations and the ratio (5β/5β + 5α) were higher than in some studies carried out in the North, Southeast and South regions of Brazil, such as the Mundaú-Manguaba Lagoon, in Alagoas, Sepetiba Bay in Rio de Janeiro, Patos Lagoon in Rio Grande do Sul and in Concepcion Bay in Chile. 48,[54][55][56] Similar comparison was also found in n-alkanes quantification at Mundaú-Manguaba and Sepetiba Bay. Patos Lagoon in Rio Grande do Sul is the largest coastal lagoon that suffers with great anthropic pressure from urban, rural and industrial activities.…”
Section: Distribution Of Sterolssupporting
confidence: 76%
“…Em Fernão Velho, muitas residências estão localizadas em zonas de deslizamentos e inundações (Melo & Lins, 2010). Cerca de 75% dos entrevistados possuem casa própria, construída em alvenaria (95%) ou taipa (5%), onde a ausência de saneamento básico e a deficiência na coleta do lixo favorecem o lançamento desses resíduos no ambiente aquático, um dos principais fatores de poluição na região (Marques, 1991;Araújo et al, 2011). As condições socioambientais e sua implicação na atividade pesqueira podem ser evidenciadas nos relatos dos informantes.…”
Section: Informações Resultados (N=25)unclassified
“…Accordingly, higher values of the sum of epicoprostanol and coprostanol in M3, as a proxy of sewage (McCalley et al, 1981), explains the positive relationships in the correlation matrix and PCA analysis to other indicators of eutrophication in mangrove soils here, including 5β:(5β + 5α), IP, and δ 15 N. The sewage contamination in M3 was further indicated by the coprostanol:cholesterol ratios (chop:cho) higher than 1.0 (Mudge and Bebianno, 1997) and coprostanol:cholestanol 5β:(5β + 5α) higher than 0.5 (Santos et al, 2008), as reported in tropical coastal aquatic sediments receiving high sewage discharges (Frena et al, 2016;dos Reis Souza et al, 2020). This limit of 5β:(5β + 5α) ratio of 0.5 for sewage pollution is assumed lower at tropical than non-tropical latitudes due to higher microbial activity with increasing temperature (Araujo et al, 2011).…”
Section: Anthropogenic Variations In Sources Composition and Diagenes...mentioning
confidence: 84%